Antioxidant-Rich Amaranth Varieties, Arka Samraksha and Arka Varna - B Varalakshmi (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2011)
Amaranth improvement in India hither to was concerned with development of high-yielding varieties, and hardly any research efforts have been made for its nutritional improvement. Keeping this in view, at Indian Institute of Horticultural Research two high-yielding amaranth varieties, Arka Samraksha and Arka Varna with high antioxidant activity, low amounts of nitrates and oxalates were developed using modified bulk method of selection from segregating population of the crosses IIHR-4 x IIHR-70 and IIHR-7 x IIHR-30 . Arka Samraksha is a high-yielding (10.9 t/ha in 30-35 days), pulling-type variety with green leaves and stem, antioxidant activity of 499mg (AEAC units) and minimum nitrate content of 27.3 mg and 1.34 g oxalates per 100 g fresh leaf weight. Arka Varna also a pulling type, high-yielding variety (10.6 t/ha in 30-35 days) with green leaves and a pink stem, high antioxidant activity of 417 mg (AEAC units), low nitrate content of 37.6 mg and 1.42 g oxalates per 100 g fresh leaf weight.